2021
DOI: 10.5194/bg-18-3053-2021
|View full text |Cite
|
Sign up to set email alerts
|

Carbon export and fate beneath a dynamic upwelled filament off the California coast

Abstract: Abstract. To understand the vertical variations in carbon fluxes in biologically productive waters, four autonomous carbon flux explorers (CFEs), ship-lowered CTD-interfaced particle-sensitive transmissometer and scattering sensors, and surface-drogued sediment traps were deployed in a filament of offshore flowing, recently upwelled water, during the June 2017 California Current Ecosystem – Long Term Ecological Research process study. The Lagrangian CFEs operating at depths from 100–500 m yielded carbon flux a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…The exclusion of PISCES mesozooplankton (ZOO2) from the comparison increases model-observation mismatch, with BGC-Argo LPOC exceeding PISCES estimates around 2-fold, although the high correlation remains (r = 0.76, p< 10 −10 ). Imaging devices mounted on BGC-Argo floats may provide a more accurate quantification of LPOC, allowing for the separation of detrital LPOC (Trudnowska et al, 2021) from mesozooplankton and micronekton (Haëntjens et al, 2020) and the separa-tion and quantification of particle classes contributing to flux across the complete particle spectrum (Bourne et al, 2021).…”
Section: Correspondence Between Observed and Simulated Poc Fractionsmentioning
confidence: 99%
“…The exclusion of PISCES mesozooplankton (ZOO2) from the comparison increases model-observation mismatch, with BGC-Argo LPOC exceeding PISCES estimates around 2-fold, although the high correlation remains (r = 0.76, p< 10 −10 ). Imaging devices mounted on BGC-Argo floats may provide a more accurate quantification of LPOC, allowing for the separation of detrital LPOC (Trudnowska et al, 2021) from mesozooplankton and micronekton (Haëntjens et al, 2020) and the separa-tion and quantification of particle classes contributing to flux across the complete particle spectrum (Bourne et al, 2021).…”
Section: Correspondence Between Observed and Simulated Poc Fractionsmentioning
confidence: 99%
“…Bourne et al. (2021) found these pellets in Cycle MBF‐Up were full of diatom frustules and fragments. We found that ∼9% of the bSi inventory at Cycle MBF‐Up is exported to 150 m, whereas ∼24% is exported at Cycle MBF‐AF.…”
Section: Discussionmentioning
confidence: 99%
“…The same is true for bSi, except for at Cycle MBF-Up in the ∼100 and 150 m traps, which is likely a result of the production of anchovy fecal pellets (Figure 11). Bourne et al (2021) found these pellets in Cycle MBF-Up were full of diatom frustules and fragments. We found that ∼9% of the bSi inven tory at Cycle MBF-Up is exported to 150 m, whereas ∼24% is exported at Cycle MBF-AF.…”
Section: Length Scales and Export Efficiencymentioning
confidence: 95%
“…It is also useful to define a second variant of atn for the situation where the illuminating light source is uncollimated and the detector has a wide acceptance angle. This is the case if atn is measured using a camera (Bishop et al 2016; Bourne et al 2019, 2021). Here, we adopt the name atnKd which is analogous to the downward, diffuse attenuation coefficient K d ( K d ( z ) = −d/dz ln( E d ( z )), where E d ( z ) is the depth‐resolved plane irradiance; Mobley 2022).…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…Occasionally, profiling floats equipped with beam transmissometers (Bishop et al 2004; Bishop and Wood 2009; Estapa et al 2013, 2017, 2019 b ) or upward‐looking cameras (Bishop et al 2016; Bourne et al 2019, 2021) are used as optical sediment traps (OSTs), providing proxy measurements that are specific to gravitational POC flux and can be used under steady‐state conditions. In the OST method, sinking particles are intercepted by the sensor itself (the upward‐facing optical window of a vertically mounted transmissometer or camera) and the rate of change in the measured light attenuance provides the proxy for flux.…”
mentioning
confidence: 99%